Life satisfaction, positive affect, depression and anxiety symptoms, and their relationship with sociodemographic, psychosocial, and clinical variables in a general elderly population sample from Chile - Saldivia, Sandra; Aslan, Joseph; Cova, Félix; Bustos, Claudio; Inostroza, Carolina; Castillo-Carreño, Anabel (Frontiers in Psychiatry, 2023)
Background: To describe the relationship between life satisfaction, positive affect, depression, and anxiety symptoms with sociodemographic, psychosocial, and clinical variables, and to identify the relative importance of these predictor groups. Methods: Life satisfaction (SWLS), positive affect (PANAS), depressive (PHQ-9), and anxiety (GAI) symptoms and their association with sociodemographic, psychosocial, and clinical variables were evaluated in a multistage, random general population sample of fully functioning people, 60-80 years old, living in the Concepción province and Gran Santiago, Chile (n=396). Weighted multiple regression analysis was performed, considering the complex sample structure with age group, sex, and geographical area, complemented with general and conditional dominance analyses to estimate the relevance of the predictor groups. Results. Significant associations were found with the geographical area, sex, age, education level, household members, having a partner, employment status, caregiver status, economic satisfaction, presence of chronic diseases, medication, and alcohol use. Satisfaction with health was the most important predictor for positive affect (p<0.001), depressive (p<0.001) and anxiety (p<0.001) symptoms and alcohol use was the most significant predictor for life satisfaction (p<0.001). Conclusions: Simultaneously studying the positive and negative dimensions of well-being and mental health of older adults allows for a more comprehensive perspective of the challenges of this stage of life. This study accounts for previously unknown associations and contributes to the identification of common and specific predictors on both dimensions.